Endometriose – gynäkologische Diagnostik und Therapie: Was sollten Schmerzmediziner*innen wissen? - Burghaus, Stefanie; Beckmann, Matthias (Schmerz, 2021)
Background: Endometriosis is one of the most common diseases in women of reproductive age. Despite characteristic symptoms such as dysmenorrhea, chronic abdominal pain, dysuria, dyschezia and dyspareunia, the average latency until diagnosis is around 10 years. In addition to the individual limitations, the disease also has economic and health policy relevance. The complaints are followed by reductions in working hours, cyclically recurring short-term sick leave or presenteeism with reduced performance. Objective: An overview of the main recommendations of the S2k guideline on the diagnosis and treatment of endometriosis. Material and methods: For the S2k guideline “Diagnostics and therapy of endometriosis”, a systematic literature search was conducted in PubMed and Cochrane according to a defined algorithm and over a period of more than 5 years, from 01.01.2014 to 31.12.2018. For the evaluation, 322 publications, including systematic reviews, meta-analyses and randomized controlled trials were considered and these were assessed by 41 mandate holders and representatives from 25 Association of the Scientific Medical Societies in Germany (AWMF) and non-AWMF professional societies, organizations, associations and working groups of the German Society for Gynecology and Obstetrics (DGGG), as well as two patient target groups. Results: In a structured consensus process, 48 recommendations and 27 statements were formulated, which are presented in extracts in this paper. Discussion: Interdisciplinary cooperation is essential in the treatment of patients with (suspected) endometriosis. This team should include all necessary disciplines in a cross-sectoral network. This is most likely to be achieved in a certified structure.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Classification/endometriosis; Interdisciplinary care team; Laparoscopy; Progestins; Ultrasonography; transvaginal